AN ANALYSIS OF IMPERATIVE SENTENCES IN SUMBAWANESE - Novi Yuniarsi; Supriadin Supriadin; Rahmawati Rahmawati (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2019)
Abstract: This research aimed to investigate the imperative sentences in Sumbawanese used by the participants in informal conversation based on the types, functions, and markers. As the sample, this research taken ten participants who were the native speakers of Sumbawanese. In conducting this research, the researcher used qualitative method. The data were taken through observation, video recorder, and field note. This research found that the types of imperative sentences in Sumbawanese are positive and negative imperative sentences. Positive imperative sentences divided into two such as positive imperative sentences with a noun as a direct address and positive imperative sentences without a noun as a direct address. While one is also divided into two, there are negative imperative sentences with a noun as a direct address and negative imperative sentence without a noun as a direct address. From all of the types of imperative sentences, the participants tend to use the positive imperative sentences with a noun as a direct address as their daily sentences in conversation. It also found that there are seven functions of imperative sentences in Sumbawanese such as imperative sentences as command, imperative sentences as request, imperative sentences as invitation, imperative sentences as suggestion, imperative sentences as advice, imperative sentences as prohibition, and imperative sentences as compulsion. However, the participants tend to use the imperative sentences as command in their conversation. The last, based on the seven markers all of imperative sentence, Sumbawa people all of them, but they dominantly used command markers of imperative sentences in their daily conversation.Abstrak: Penelitian ini bertujuan untuk mengetahui kalimat-kalimat perintah dalam bahasa Sumbawa yang digunakan masyarakat dalam percakapan informal berdasarkan jenis, fungsi, dan penanda. Sebagai sample, penelitian ini melibatkan   sepuluh partisipan penutur asli bahasa Sumbawa. Penelitian ini adalah penelitian kualitatif. Data penelitian diperoleh dengan cara observasi, video rekaman, dan catatan lapangan. Hasil penelitian ini bahwa bentuk kalimat imperatif dalam bahasa Sumbawa terdiri dari kalimat imperatif positif dan negatif. Kalimat imperatif positif dibagi menjadi dua yaitu kalimat imperatif menggunakan kata benda untuk panggilan langsung dan kalimat imperatif tidak menggunakan kata benda untuk panggilan secara langsung. Hal ini sama halnya dengan ungkapan kalimat imperatif negatif. Dari sekian bentuk kalimat imperatif, orang sumbawa cenderung menggunakan kalimat imperatif positif menggunakan kata benda dengan panggilan secara langsung ketika berkomunikasi sehari-hari. Ditemukan juga bahwa ada tujuh fungsi kalimat imperatif dalam bahasa Sumbawa yaitu kalimat imperatif untuk umum, meminta, mengundang, saran, nasehat, larangan, dan mewajibkan. Akan tetapi orang sumbawa cenderung menggunakan kalimat imperatif umum ketika berkomunikasi. Dari aspek penanda kalimat imperatif, orang Sumbawa  menggunakan semua penanda tersebut, namun penanda perintah dalam kalimat imperatif adalah yang paling digunakan oleh masyarakat dalam percakapan sehari-hari.